PERBANDINGAN SEBELUM DAN SESUDAH ADANYA “PERATURAN PEMERINTAH NOMOR 46 TAHUN 2013” DAN PENGARUHNYA TERHADAP PAJAK PERUSAHAAN (STUDI KASUS PADA PT. DBL) - Siti Ratna Sari Dewi (Universitas Pamulang, 2019)
AbstractThe purpose of this study is to find out how much the amount of tax issued and whether there is a difference in the amount of tax issued by the company before and after the existence of